2011
DOI: 10.2139/ssrn.1932247
|View full text |Cite
|
Sign up to set email alerts
|

The Food Crises: A Quantitative Model of Food Prices Including Speculators and Ethanol Conversion

Abstract: Increases in global food prices have led to widespread hunger and social unrest-and an imperative to understand their causes. In a previous paper published in September 2011, we constructed for the first time a dynamic model that quantitatively agreed with food prices. Specifically, the model fit the FAO Food Price Index time series from January 2004 to March 2011, inclusive. The results showed that the dominant causes of price increases during this period were investor speculation and ethanol conversion. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
79
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(84 citation statements)
references
References 85 publications
0
79
0
2
Order By: Relevance
“…The wave of social unrest known as the Arab Spring was preceded by food riots, the result of spiking global food prices. In turn, the cause of the fluctuations in the food markets can be traced to commodities deregulation in the US, which allowed for rampant speculation, as well as ethanol fuel mandates which promoted the inefficient conversion of food into fuel (Lagi, Bertrand and Bar-Yam 2011a;Merchant 2014;Lagi et al 2011b). Similar policy decisions in the US precipitated the 2008 economic crisis, as well as other market crashes (Harmon et al 2011;Harmon et al 2010).…”
Section: Global Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wave of social unrest known as the Arab Spring was preceded by food riots, the result of spiking global food prices. In turn, the cause of the fluctuations in the food markets can be traced to commodities deregulation in the US, which allowed for rampant speculation, as well as ethanol fuel mandates which promoted the inefficient conversion of food into fuel (Lagi, Bertrand and Bar-Yam 2011a;Merchant 2014;Lagi et al 2011b). Similar policy decisions in the US precipitated the 2008 economic crisis, as well as other market crashes (Harmon et al 2011;Harmon et al 2010).…”
Section: Global Systemsmentioning
confidence: 99%
“…Recent global crises, including the global financial crisis, the global food crisis, social unrest including the Arab Spring, and the Ebola epidemic and other pandemics, have demonstrated that global connectivity leads to vulnerabilities due to the high rate of global travel, and the rapid propagation of economic and social influences (Lagi, Bertrand and Bar-Yam 2011a;Merchant 2014;Lagi et al 2011b;Harmon et al 2011;Harmon et al 2010;Rutherford et al 2014;Rauch and Bar-Yam 2006). Many of the key problems today have to do with 'indirect effects' of human activities that may have substantial destructive effects on the human condition.…”
mentioning
confidence: 99%
“…In early 2010 and late 2011, even higher food prices corresponded with riots in Mauritania, Uganda and other countries associated with the Arab Spring [44]. The root cause of these spikes in food prices is still being debated, although most researchers agree that resource competition due to biofuel production is a factor [45,46]. One thing is certain, as the demand for agricultural products increases due to rising biofuel production, growing populations and the improved economic status of billions, more will be asked of our land resources.…”
Section: Increased Demand For Agricultural Products: Rising Populatiomentioning
confidence: 99%
“…The role of speculators in the spike of food prices has been hotly contested but a recent study by Lagi et al [22] has thrown new light and shows the impact of speculators in price increase has been greater than previously thought, as illustrated in Figure 1.…”
Section: Food Pricesmentioning
confidence: 99%
“…Lagi et al [22] updated their previous work (2011), constructed for the first time a dynamic model that quantitatively agreed with food prices, based on the FAO Food Price Index time series from January 2004 to March 2011, and updated to February 2012. The results showed that the dominant causes of price increases during this period were investor speculation and ethanol conversion.…”
Section: Food Pricesmentioning
confidence: 99%